(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2021)
Long-acting drug delivery systems able to sustain the release of therapeutics in a controllable manner can provide several advantages in the treatment of chronic diseases. Given the high drug concentration in the reservoir, an inward osmotic fluid transport occurs across the membrane, which counters the outward diffusion of drugs. The resulting osmotic pressure buildup may be sufficient to cause the failure of implants with associated risks to patients. Confidently assessing the osmotic pressure buildup requires testing in vivo. Here, using metal and polymer additive manufacturing processes, we designed and developed implantable drug reservoirs with embedded strain sensors to directly measure the osmotic pressure in drug delivery implants in vitro and in vivo.